Analysis of the effectiveness of the distribution of zakat funds in Baitul Mal of Langsa city - Mora, Zulkarnen; Aini , Zainatun (ASNAF : Journal of Economic Welfare, Philantrophy, Zakat and Waqf, 2023)
Abstract Purpose – This research was conducted to determine the level of effectiveness and implementation of the zakat fund distribution program in improving the welfare of mustahik. Method – This research uses descriptive qualitative research. Respondents as informants in this study were 7 people and 1 person as a key figure. The data sources used in this research are primary data and secondary data consisting of observation, interviews, and documentation.The criteria for being used as informants are people who are members of Baitul Mal Langsa. Results – The results showed that the distribution of zakat funds has been running effectively and the funds are channeled through 7 asnaf program criteria, namely AsnafFakir, Asnaf Miskin, Asnaf Muallaf, Asnaf Fiisabilillah, Asnaf Ibnu Sabil, AsnafGharim and Asnaf Amil, and have a big impact on suppressing the movements of moneylenders and increasing mustahik trust. Limitations – This study was considered as a cause-and-effect study with a single observation object. Practical Implications – This research shows the need for supervision in the distribution of zakat funds in Baitul Mal Kota Langsa so that the funds are channeled.